Lessons from sports: What corporate management can learn from sports management - Gerd Nufer; André W. Bühler (Hochschule Reutlingen, School of International Business (SIB), 2011)
Sporting organizations increased their degree of professionalism step by step within the last decades because being just a pure sporting organization is not enough. These days, sporting bodies and codes have to be professional in order to survive in an extremely competitive mar-ket. Therefore, sporting organizations adopt and adapt management practices and techniques, human resource approaches and marketing strategies. They learn from corporate businesses of other industry sectors. However, in this paper we seek to examine the opposite perspective: What can a company learn from sports? In which ways can sports management serve as a role model for corporate management? We start with the description of some existing parallels between sports and corporate management in general. We then focus on how sporting organizations make use of globalization, human resources and marketing. Especially with regard to human resources and marketing, we will see that sports is far ahead of today's corporate management in these areas - there is a lot to learn for corporate management from the strategies and approaches used in the world of sports.
urn:nbn:de:bsz:21-opus-54397
Keywords: 650